Jadhr al-Aṣam Menurut al-Khafrī: Terjemahan Risālah ‘Ibrah al-Fuḍalā’ fī Ḥall Shubhah Jadhr al-Aṣam dan Analisis Kritikannya Terhadap al-Dawwānī: Liar Paradox (Jadhr al-Aṣam) according to al-Khafrī: Translation of Risālah ‘Ibrah al-Fuḍalā’ fī Ḥall Shubhah Jadhr al-Aṣam and Analysis of His Criticism on al-Dawwānī - Mohd Zaidi, Muhammad Amzar Hanif; Khairuddin, Wan Haslan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Jadhr al-Aṣam (Liar Paradox) is not a foreign issue among Islamic scholars, particularly the mutakallimūn and manāṭiqah of the past, who examined this paradox in depth, not only by exploring its formulations and implications but also by proposing solutions and evaluating their impact on the discourse of kalām and logic. One such scholar, Shams al-Dīn Muḥammad al-Khafrī, a logician and polymath, addressed this centuries-old paradox in his writings. His rejection of the solutions proposed by Jalāl al-Dīn al-Dawwānī warrants further investigation to derive insights from both thinkers, particularly for developing a new framework for understanding logic (manṭiq) and critical thinking in the Malaysian context. This study aims to identify al-Dawwānī’s proposed solutions, summarise al-Khafrī’s critiques, and analyse the arguments presented by both scholars. It also includes a translation and brief analysis of Risālah ʿIbrah al-Fuḍalāʾ fī Ḥall Shubhah Jadhr al-Aṣam by Shams al-Dīn al-Khafrī. In this treatise, al-Khafrī questions the ontological status of Jadhr al-Aṣam, examines the nature of self-referential statements, and asserts that the paradox remains a khabar (declarative statement) rather than an inshāʾ (performative utterance). The methodology employed involves collecting data and conducting content analysis of the relevant classical texts.